38 Understanding learning needs and ways of engaging with web apps: the development of an innovative educational web-based application for the respect process. Issue 3 (1st September 2017) - Soosaipillai, Gehan; Stables, Tom; Pfeifer, Nadine; Mooney, Jenny; Archer, Stephanie; Darzi, Ara; Stirling, Lucy Caroline
Abstract : Introduction: Optimal care of patients who are at risk of acute deterioration requires compassionate and competent communication and shared decision making (Department of Health 2008). ReSPECT (Recommended Summary Plan for Emergency Care and Treatment) is a new national process that creates personalised recommendations for a person's clinical care in a future emergency in which they are unable to make or express choices (ReSPECT Steering Group 2017). The ReSPECT Educational Material Project Operations Group at UCLPartners is creating an innovative web-app to support health and care staff of all disciplines, in all settings, in the ReSPECT process. Aims: Understand user learning needs and utilise their experience and knowledge to inform the content of the web-app. Methods: We conducted interviews and focus groups with 31 health and care staff from a range of settings, in the NHS, third and private sectors, including a NHS trust that has implemented ReSPECT. We explored the pedagogy of online learning and the reality of engaging in such conversations. Results: Users need to see representations of themselves to learn from and connect with the material. Apprenticeship learning models that encourage reflection are the most effective for the difficult conversations. Length and credibility of information are key factors in engaging with learning materials. Online learning is often rushed through to get to the evaluation part. Conclusion: These insights are guiding the development of the web-app. We will use iterative-design to test the content and improve usability. The educational impact of the web-app and impact on patient outcomes will be evaluated in future studies. References: . Department of Health, 2008. End of Life Care Strategy – promoting high quality care for all adults at the end of life, . ReSPECT Steering Group, 2017. ReSPECT (Recommended Summary Plan for Emergency Care and Treatment). Available at: http://www.respectprocess.org.uk.